The effect of using an active learning strategy in teaching the English language on the achievement level of primary school students - Al-Ghamdi, Shorouq Ali; Al-Oweidi, Afrah Hafiz (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the effect of using an active learning strategy in teaching the English language on the level of achievement of primary school students. To achieve the study objectives, the researcher used the descriptive analytical approach through utilizing the questionnaire to collect data from the targeted sample. The study population included all primary stage female teachers in Bisha Governance, who account for (109) teachers, where the researcher conducted a full survey of the population. The results of the study showed that using moral incentives to promote positive behavior among primary school students leads to improving their academic achievement, active learning increases classroom interaction between teachers and primary school students. In light of the obtained results, the researcher recommended the utilization of an active learning strategy in teaching the English language, and that English teachers should continuously focus on updating their teaching techniques and methods to boost students learning.